The Potential of Social Entrepreneurship in Tourism - Waligóra , Anna (Studia Oeconomica Posnaniensia, 2018)
There is evidence in the theory and practice of managing for the possibility of involving social enterprises in the development of the tourism industry. This is evidenced by both historical data from Poland and examples of such practices from other countries. The study these phenomena there was used documents analysis and analysis of other existing sources. Studies show that the inclusion of social enterprises in economic activity in the field of tourism is, on the one hand, a historical fact. On the other hand, it is also a chance to recreate the patterns of management in this field that match the expectations of modern and postmodern tourists.